2022
DOI: 10.1111/jocn.16447
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of radiofrequency scanning technology in preventing retained surgical items: An integrative review

Abstract: Aims and Objectives:To synthesise evidence on the effectiveness of radiofrequency (RF) scanning technology as an adjunct to manual counting protocols in preventing retained surgical items (RSIs) in the operating room.Background: Despite the implementation of rigorous manual counting protocols, RSIs remain one of the most common reported sentinel events in operating theatres that lead to adverse patient outcomes. Design: An integrative review.Methods: This review was guided by the Whittemore and Knafl (2005) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(214 reference statements)
0
3
0
Order By: Relevance
“…By reviewing the current peer-reviewed literature, the authors qualitatively evaluated the evidence synthesizing the effectiveness of radiofrequency scanning technology as an adjunct to manual counting protocols in preventing residual surgical items in the operating room. Organized around four dimensions, the authors concluded that radiofrequency scanning technology is effective in preventing surgical debris and results in significant cost savings (Peng et al, 2023). This article provides theoretical support for a wide range of healthcare decision-makers to improve the status of the operating room.…”
Section: Comment On: the Effectiveness Of Radiofrequency Scanning Tec...mentioning
confidence: 86%
“…By reviewing the current peer-reviewed literature, the authors qualitatively evaluated the evidence synthesizing the effectiveness of radiofrequency scanning technology as an adjunct to manual counting protocols in preventing residual surgical items in the operating room. Organized around four dimensions, the authors concluded that radiofrequency scanning technology is effective in preventing surgical debris and results in significant cost savings (Peng et al, 2023). This article provides theoretical support for a wide range of healthcare decision-makers to improve the status of the operating room.…”
Section: Comment On: the Effectiveness Of Radiofrequency Scanning Tec...mentioning
confidence: 86%
“…The thorough analysis presented in the literature [ 3 , 4 , 5 , 6 , 7 ] documents that the human factor that participates in a standard counting protocol increasing vigilance and communication among staff [ 3 , 8 ] cannot fully eliminate hard RSI events. It implies that the classical methods (standard counting, presence of a trainee—however, reducing an occurrence of RSI by two-thirds [ 6 ]) cannot prevent these adverse patient outcomes [ 9 ]. It substantiates that a parallel implementation of more sophisticated methods would be required.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency scanning technology represents a very efficient method for the non-invasive identification of radiopaque items [ 5 , 7 , 8 , 9 , 10 ]. The problem is that not all medical items are able to absorb the radiant energy of an electromagnetic field due to their radiolucency (electromagnetic radiation passes through such particular materials) caused by their low electron density.…”
Section: Introductionmentioning
confidence: 99%